2019
DOI: 10.1186/s40249-019-0597-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Anopheles gambiae sensu lato larvae in the urban environment of Yaoundé, Cameroon

Abstract: Background The rapid and unplanned urbanization of African cities is considered to increase the risk of urban malaria transmission. The present study objective was to assess factors influencing the spatio-temporal distribution of Anopheles gambiae s.l. larvae in the city of Yaoundé, Cameroon. Methods All water bodies were checked once every 2 months for the presence of mosquito larvae from March 2017 to May 2018 in 32 districts of Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 74 publications
5
20
0
Order By: Relevance
“…As also reported elsewhere, this study found that most of the potential breeding habitats were manmade in origin and had higher larval density than natural habitats ( Djamouko-Djonkam et al, 2019 ; Aik et al, 2019 ), this highlights the potential of public health education in controlling mosquito borne diseases by advocating avoidance on creating potential breeding sites. But also, most of the manmade breeding sites tend to cluster around human settlement as observed in this study that more than three quarter of all the potential breeding sites were within less than 100 m from human settlements and they were more likely to have high larval density as compared to those located more than 100 m from human dwelling.…”
Section: Discussionsupporting
confidence: 85%
“…As also reported elsewhere, this study found that most of the potential breeding habitats were manmade in origin and had higher larval density than natural habitats ( Djamouko-Djonkam et al, 2019 ; Aik et al, 2019 ), this highlights the potential of public health education in controlling mosquito borne diseases by advocating avoidance on creating potential breeding sites. But also, most of the manmade breeding sites tend to cluster around human settlement as observed in this study that more than three quarter of all the potential breeding sites were within less than 100 m from human settlements and they were more likely to have high larval density as compared to those located more than 100 m from human dwelling.…”
Section: Discussionsupporting
confidence: 85%
“…funestus are permanent or semi-permanent water collections with emergent vegetation [26]. Its presence in the city of Yaoundé may result from the presence of marshland covered with emerging vegetation along the Mfoundi and Mefou rivers [21]. Anopheles funestus is widely distributed across the country [3] and in most rural settings where it has been reported, it may sustain very high levels of malaria transmission [2,7,16,61].…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of species might result from the high variety of breeding habitats in Mendong compared to Nsam with the presence of puddles, lakes, rivers, and swamps, which could be excellent habitats for a variety of mosquito species [2,4,11,21]. Seasonal fluctuations in the biting densities of An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the spatial distribution of mosquito breeding habitats is needed to enable monitoring and targeting of hotspot areas where vector populations are persistent. The development of Geographic Information Systems (GIS) mapping technology provides high-resolution maps of mosquito distribution or transmission risks, which could improve malaria surveillance system [8,9].…”
Section: Introductionmentioning
confidence: 99%